Classification of brain tumours from MR spectra: the INTERPRET collaboration and its outcomes. (December 2015) - Julià‐Sapé, Margarida; Griffiths, John R.; Tate, Rosemary A.; Howe, Franklyn A.; Acosta, Dionisio; Postma, Geert; Underwood, Joshua; Majós, Carles; Arús, Carles
Abstract : The INTERPRET project was a multicentre European collaboration, carried out from 2000 to 2002, which developed a decision‐support system (DSS) for helping neuroradiologists with no experience of MRS to utilize spectroscopic data for the diagnosis and grading of human brain tumours. INTERPRET gathered a large collection of MR spectra of brain tumours and pseudo‐tumoural lesions from seven centres. Consensus acquisition protocols, a standard processing pipeline and strict methods for quality control of the aquired data were put in place. Particular emphasis was placed on ensuring the diagnostic certainty of each case, for which all cases were evaluated by a clinical data validation committee. One outcome of the project is a database of 304 fully validated spectra from brain tumours, pseudotumoural lesions and normal brains, along with their associated images and clinical data, which remains available to the scientific and medical community. The second is the INTERPRET DSS, which has continued to be developed and clinically evaluated since the project ended. We also review here the results of the post‐INTERPRET period. We evaluate the results of the studies with the INTERPRET database by other consortia or research groups. A summary of the clinical evaluations that have been performed on the post‐INTERPRET DSS versions is also presented. Several have shown that diagnostic certainty can be improved for certain tumour types when the INTERPRET DSS is used in conjunction with conventional radiological image interpretation. About 30 papers concerned with the INTERPRET single‐voxel dataset have so far been published. We discuss stengths and weaknesses of the DSS and the lessons learned. Finally we speculate on how the INTERPRET concept might be carried into the future. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : The INTERPRET project was a multicentre European collaboration, carried out from 2000 to 2002, which developed a decision‐support system (DSS) to help neuroradiologists utilize MRS data for diagnosing and grading human brain tumours. Its development involved gathering a large collection of MR spectra of brain tumours from seven centres. We review here the results of the studies utilizing the INTERPRET data that have been performed during subsequent years, and also the clinical evaluations of later developments of the INTERPRET DSS.